Plant Growth and Morphogenesis under Different Gravity Conditions: Relevance to Plant Life in Space - Takayuki Hoson (Life, 2014)
The growth and morphogenesis of plants are entirely dependent on the gravitational acceleration of earth. Under microgravity conditions in space, these processes are greatly modified. Recent space experiments, in combination with ground-based studies, have shown that elongation growth is stimulated and lateral expansion suppressed in various shoot organs and roots under microgravity conditions. Plant organs also show automorphogenesis in space, which consists of altered growth direction and spontaneous curvature in the dorsiventral (back and front) directions. Changes in cell wall properties are responsible for these modifications of growth and morphogenesis under microgravity conditions. Plants live in space with interesting new sizes and forms.